In-vivo thrombolytic efficacy of RGD modified protein-polymer conjugated urokinase nanogels - Xia Liu (Elsevier, 2021)
It has been shown that an arginine-glycine-aspartic acid (RGD) modified pH-triggered delivery system for the urokinase-type plasminogen activator (uPA) is resistant to enzymatic degradation and improves thrombolytic ability in vitro. Herein, we aimed to compare the thrombolytic efficacies of uPA-oxidized dextran (Oxd)-RGD and uPA using a rat model of middle cerebral ischemia occlusion (MCAO) in vivo. We found that the uPA-Oxd conjugates delayed the release of active uPA after MCAO. Thus, the rats treated with uPA-Oxd-RGD showed significantly decreased neurological deficits and infarct volume compared with those of the rats treated with uPA alone after MCAO. Furthermore, the administration of uPA-Oxd-RGD attenuated blood–brain barrier disruption and downregulated matrix metalloproteinase expression while upregulating the expression of tight junction proteins. In addition, uPA-Oxd-RGD inhibited apoptosis by suppressing pro-apoptotic caspase expression. These results suggest that the administration of uPA-Oxd-RGD is a more effective intervention in an MCAO model than uPA alone and that the pH changes in the brain tissue after an ischemic stroke may be a novel thrombolytic target.